The European Union in Crisis: Explorations in Representation and Democratic Legitimacy - Demetriou, Kyriakos N (Springer, 2015)
This volume is a comprehensive and rigorous exploration of intertwined issues surrounding the EU's democracy and legitimacy, written in the turbulent context of the financial crisis. The chapters are woven together under four interconnected thematic sections that examine: rapidly growing national euroscepticism; the Economic Monetary Union and its legitimacy; the future of EU integration; and democratic deficit(s) across its internal & external structure. The volume presents an authoritative collection of research results and surveys by experts in various disciplines related to the EU, and is addressed to researchers and students examining EU governance, representation and accountability, as well as practitioners across a multiplicity of fields.